Mengenal Hadis dan Fungsinya sebagai Penjelas Al-Qur’an - Mujib, Ahmad; Anshory, M. Isa (Lembaga Yasin AlSys, 2025)
This article discusses the definition of hadith, its classification, and its role in elucidating the Qur’an as the primary source of Islamic teachings. Hadith encompasses everything attributed to the Prophet Muhammad (peace be upon him), including his sayings (qauli), actions (fi’li), and approvals (taqrir), and holds the position of the second principal source of Islamic teachings after the Qur’an. The classification of hadith is crucial for helping Muslims evaluate its authenticity, understand its context, and distinguish between various types. Fundamentally, hadith functions as an explanation and elaboration of Qur’anic verses, providing legal boundaries, rulings, and practical guidance not explicitly stated in the text of the Qur’an. Moreover, hadith serves as a primary reference for applying Islamic teachings in daily life, encompassing both worship (ibadah) and social interactions (muamalah). Thus, the existence of hadith is essential to ensuring the proper implementation of Islamic law in accordance with the guidance of the Prophet Muhammad (peace be upon him) as the conveyor of divine revelation.